The Role of School Culture in Nurturing Pancasila Profile in Elementary School Students - Vera Yuli Erviana; Fajar Oktavia Rahma (Universitas Pendidikan Ganesha, 2025)
School culture serves as a fundamental foundation for fostering the Pancasila Student Profile. The curriculum change in Indonesia was a response to the impact of the COVID-19 pandemic, which caused learning loss at various educational levels. As a recovery effort, the government designed an Emergency Curriculum that proved effective and was later developed into the Merdeka Curriculum (Independent Curriculum). This curriculum focuses on strengthening character education through the implementation of the Pancasila Student Profile, which is realized within school culture. This study aims to analyze the implementation of the Merdeka Curriculum in shaping the Pancasila Student Profile through the reinforcement of school culture. The research employed a qualitative descriptive approach with participants consisting of the principal, teachers, and elementary school students. Data were collected through interviews, observations, and documentation, then analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings indicate that the implementation of the Merdeka Curriculum successfully internalizes the values of the Pancasila Student Profile through daily activities, collaborative learning, and extracurricular programs that foster independence, religiosity, tolerance, and integrity. In conclusion, the Merdeka Curriculum effectively develops students’ character and soft skills through a school culture oriented toward Pancasila values. The implications of this study suggest that strengthening school culture can serve as an effective strategy for integrating character education into the curriculum and as a model for cultivating the Pancasila Student Profile that can be adapted by other schools to enhance the quality of national education.